Linguistic Characterization of Text on Environmental Topics - A. V. Moiseenko (Научный диалог, 2019)
The article discusses the structural and semantic features of a regional newspaper text on environmental topics. The material contains 30 texts from the socio-political newspaper “Rech” of the city of Cherepovets, Vologda Oblast, published during 2017 - the Year of Ecology in Russia. It is shown that the newspaper text on environmental topics has the structure of an inverted pyramid, when important information is presented at the beginning of the article, and detailing is presented in the second part; the photographs accompanying the texts have a different visual-grammatical structure and can be interpreted as one-part and two-part sentences. In the semantic aspect, it is revealed that a larger number of contextual synonymous pairs than sets are formed; gradual antonyms are used; lexical units are included that fix the anthropocentric model of the interaction of man and nature. It is identified that there is a two-way interaction between the environmental event and the text: the event is the basis for creating the text, and vice versa, a newspaper text covering an environmental problem may precede one event or another. It is indicated that the newspaper text on environmental topics is characterized by a homogeneous presentation of the material, anthropocentricity and polyphonicity; softening the presentation of problematic information is achieved through the use of literary synonyms, gradual antonyms and relevant illustrations.